Perancangan Sistem Informasi Produksi Dengan SCM Pada Toko Konveksi - Radiyan Rahim; Dinul Akhiyar; Nori Sahrun (KLIK: Kajian Ilmiah Informatika dan Komputer, 2022)
The overall goal of the elements in the supply chain is to provide finished goods to the market while increasing company profits. Supply Chain Management includes all activities, raw storage materials, work-in-process inventory and goods ready from start to finish users. Convection is a marchendaise production site related to clothing or clothing needs, or more modernly related to fashion production with a certain minimum quantity. Convection is an industry that is very concerned about the production process to get good quality and timeliness. With the existence of a technology-based production system at the convection of the Toko Konveksi will help in increasing the effectiveness of the production process of goods with good quality and on time. The development of this system is designed through several stages, starting from the stage of collecting data, analyzing and designing applications, making programs and implementing applications. The end result of this system is a web-based application that can be used by convection and customers in more efficient transactions